2022
DOI: 10.3389/fneur.2022.1040975
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-mediated sleep phase modulation ameliorates motor and cognitive performance in a chronic blast-injured mouse model

Abstract: Multiple studies have shown that blast injury is followed by sleep disruption linked to functional sequelae. It is well established that improving sleep ameliorates such functional deficits. However, little is known about longitudinal brain activity changes after blast injury. In addition, the effects of directly modulating the sleep/wake cycle on learning task performance after blast injury remain unclear. We hypothesized that modulation of the sleep phase cycle in our injured mice would improve post-injury t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Another bTBI and PSG study in rats reported 24 h post-injury hypersomnia effects and did not show persistent effects or determine hallmarks of bTBI sequalae ( Mountney et al, 2021 ). A third study found hypersomnia and EEG delta/theta ratios but only assessed within 1 week post-injury ( Bibineyshvili et al, 2022 ).…”
Section: Models Of Tbi and Sleep Disturbancesmentioning
confidence: 99%
“…Another bTBI and PSG study in rats reported 24 h post-injury hypersomnia effects and did not show persistent effects or determine hallmarks of bTBI sequalae ( Mountney et al, 2021 ). A third study found hypersomnia and EEG delta/theta ratios but only assessed within 1 week post-injury ( Bibineyshvili et al, 2022 ).…”
Section: Models Of Tbi and Sleep Disturbancesmentioning
confidence: 99%